Effect of iodine nutritional status on the recurrence of hyperthyroidism and antithyroid drug efficacy in adult patients with Graves’ disease: a systemic review - Xie, Qingxing; Zhang, Xinyi; Ma, Jinfang; Lu, Xi; Zhang, Yuwei; Tong, Nanwei (Frontiers in Endocrinology, 2023)
Xie QX, Zhang XY, Ma JF, and Lu X have nothing to declare. Tong NW has worked on clinical trials funded by Huadong Medicine Group Company Limited and received lecture fees from Novo Nordisk. However, these interests will not impair the justice and scientific nature of this study.The review was registered in NIHR PROSPERO, with the original title of "What iodine status should be maintained in patients with GD on ATD therapy" (CRD42022359451). Some changes have occurred in the inclusion and exclusion criteria, which were amended continuously in the process of searching.